Cardioprotection and its Translation: A Need for New Paradigms? Or for New Pragmatism? An Opinionated Retro- and Perspective - Gerd Heusch MD, FACC, FESC, FRCP (SAGE Publishing, 2023)
The dawn of cardioprotection by infarct size reduction originated from the idea to favourably alter the oxygen demand-supply balance of the ischaemic/infarcting myocardium by reducing the contractile determinants of its oxygen consumption. This idea is probably not correct, since the ischaemic/infarcting myocardium does not contract anyway. None of the successful initial preclinical attempts of infarct size reduction translated into clinical practice, except for timely reperfusion which has become and still is the backbone of all clinical infarct therapy up today. The idea of cardioprotection gained momentum again with the recognition of ischaemic conditioning, and a myriad of preclinical studies have identified molecules and mechanisms of such self-defence mechanism. Although there are positive clinical proof-of-concept studies, ischaemic conditioning strategies and drugs related to its signal transduction have not translated into clinical practice. We are currently trying to understand the obstacles to translation from successful preclinical studies on cardioprotection to clinical practice, but are also waiting for an innovative mechanistic breakthrough.